Análise das propriedades mecânicas de juntas sobrepostas na liga Al 6181-T4 soldadas por fricção por ponto - Parra, Bruno Serafim (2011)
Lightweight alloys, originally developed for aeronautic applications, have also shown increasing use in the automotive sector, aiming fuel consumption and reduction of production costs. In addition to this there is the increasing environmental concern that makes lightweight alloys even more attractive, due to recycling capabilities. It is important notice that parts produced with lightweight alloys may need, at some point of the production process, be joined to others parts. In the aeronautic industry the joining is made primarily by riveting while in the automotive industry RSW - Resistance Spot Welding is usually employed. These processes present some problems such as those related to metallurgical defects and the low weldability for some lightweight alloys. Within this context the FSpW - Friction Spot Welding, that is a solid state joining process, was developed at GKSS Research Centre in Germany. This process has shown great potential for applications where the already established RSW (automotive) and riveting (aircraft), present some disadvantages. In this work the applicability of this new process for the production of overlapping joints of the alloy 6181-T4, which is already used in the automotive industry, was studied. Joints were produced with different welding parameters (welding time and rotational speed) and will be submitted to mechanical characterization, by means of microhardness measurements and mechanical tests for assessment of the performance of the welds. Microstructural characterizations will be performed using optical and electron microscopy to determine the effect of the welding parameters on the final microstructure of the welds, as well as eventual defects. It will be also done a study of failure analysis, aiming the understanding of the mechanisms of fracture, correlating them with the process parameters. Sound joints with high mechanical strength and good repeatability were obtained, with better results associated to low welding time and high toll rotational speed.